Clinically-derived vagus nerve stimulation enhances cerebrospinal fluid penetrance - Kevin P. Cheng; Sarah K. Brodnick; Stephan L. Blanz; Weifeng Zeng; Jack Kegel; Jane A. Pisaniello; Jared P. Ness; Erika Ross; Evan N. Nicolai; Megan L. Settell; James K. Trevathan; Samuel O. Poore; et al. (Brain Stimulation, 2020)
Introduction: Vagus nerve stimulation (VNS) is an FDA-approved neuromodulatory treatment used in the clinic today for epilepsy, depression, and cluster headaches. Moreover, evidence in the literature has led to a growing list of possible clinical indications, with several small clinical trials applying VNS to treat conditions ranging from neurodegenerative diseases to arthritis, anxiety disorders, and obesity. Despite the growing list of therapeutic applications, the fundamental mechanisms by which VNS achieves its beneficial effects are poorly understood. In parallel, the glymphatic and meningeal lymphatic systems have recently been described as methods by which the brain maintains a healthy homeostasis and removes waste without a traditionally defined lymphatic system. In particular, the glymphatic system relates to the interchange of cerebrospinal fluid (CSF) and interstitial fluid (ISF) whose net effect is to wash through the brain parenchyma removing metabolic waste products and misfolded proteins. Objective/Hypothesis: As VNS has well-documented effects on many of the pathways recently linked to the clearance systems of the brain, we hypothesized that VNS could increase CSF penetrance in the brain. Methods: We injected a low molecular weight lysine-fixable fluorescent tracer (TxRed-3kD) into the CSF system of mice with a cervical vagus nerve cuff implant and measured the amount of CSF penetrance following an application of a clinically-derived VNS paradigm (30 Hz, 10% duty cycle). Results: We found that the clinical VNS group showed a significant increase in CSF tracer penetrance as compared to the naïve control and sham groups. Conclusion: (s): This study demonstrates that VNS therapeutic strategies already being applied in the clinic today may induce intended effects and/or unwanted side effects by altering CSF/ISF exchange in the brain. This may have broad ranging implications in the treatment of various CNS pathologies.